LEARNING DEVELOPMENT THROUGH MULTI GRADE TEACHING IN INDONESIAN TRADISONAL MUSLIM SCHOOLS - Fawait, Agus; Yuliana, Indry Ayu; Arifah, Siti Aisyatul (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to uncover facts and find learning formulas in traditional Muslim schools or better known as Islamic boarding schools which are related to multigrade classes. This research uses a qualitative phenomenological approach, data collection in this research includes observation, interviews and documentation. Data analysis uses an interactive model, while checking validity uses a triangulation method. The research results show that Multi Grade Teaching in Islamic boarding school learning begins with preparation involving material, technical and human preparation. In practice, the MGT model of learning is carried out through learning centered in the mosque. The educational interaction process that occurs at the Darul Huda Islamic boarding school is divided into two, namely educational interaction that occurs in the learning process such as the Koran, sorogan, and syawir and the learning interaction process that occurs outside the learning process such as group discussions in front of the dormitory or in the mosque foyer. Researchers suggest that further research be carried out to find a more appropriate formula for developing learning in Islamic boarding schools.